EFFEK UPWELLING TERHADAP KELIMPAHAN DAN DISTRIBUSI FITOPLANKTON DI PERAIRAN LAUT BANDA DAN SEKITARNYA - Agus, Agus (Makara Journal of Science, 2004)
The Effect of Upwelling on Distribution and Abundance of Phytoplankton in Indonesia. East Monsoon is monsoon where upwelling process happened in Banda Sea. Information about upwelling effect to the abundance and distribution of phytoplankton in Banda Sea is not known much.yet. That way has been done the investigation in August 1997 as vice of east monsoon and October 1998 as vice of transition monsoon as comparation.. The abundance and distribution data collected by taken phytoplankton sample in 100 m depth to surface by using plankton net with diameter 31 cm, 120 cm length, and eyes net size 80 µm. The results in east monsoon (August 1997) where (upwelling) still done. This correlation seen from regresi value between temperature and salinity (r2 = 84,1 %), temperature and nitrate (94,5%) In east monsoon recorded 33 phytoplankton species, composition of phytoplankton is varied more compared to transition monsoon where found 26 phytoplankton species only. In east monsoon dominance phytoplankton is Chaetoceros sp. Further analysis by using multivariate analysis, nitrate factor affect to abundance, composition, and distribution of phytoplankton.